Applications of low-cost 3D imaging techniques for the documentation of heritage objects - Morita, María Mercedes (2018)
3D image recording has reached an increasing impact on the field of cultural heritage. Applications include documentation of the state of conservation and dimensions of an object, the archaeological survey of artefacts, the dissemination of museum collections and sites, and packaging designing, among others. The 3D image acquisition techniques most commonly used are laser or structured light scanning and, increasingly, close range digital photogrammetry. In this work a 3D digitization case-study is presented in order to explore the advantages and possibilities of close range digital photogrammetry respect to scanning techniques in documentation of heritage objects. Free and low-cost software used by these techniques were tested and the quality of the results obtained in each case is analyzed. The potentiality of close range digital photogrammetry to enhance the resolution of the 3D recording is also discussed.